2016
DOI: 10.3390/ijms18010031
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin Attenuates Enhancement of Hepatic Gluconeogenesis by Inhibiting NOD Activation-Mediated Inflammation in High-Fat Diet-Treated Mice

Abstract: Recent evidence suggests that troxerutin, a trihydroxyethylated derivative of natural bioflavonoid rutin, exhibits beneficial effects on diabetes-related symptoms. Here we investigated the effects of troxerutin on the enhancement of hepatic gluconeogenesis in high-fat diet (HFD)-treated mice and the mechanisms underlying these effects. Mice were divided into four groups: Control group, HFD group, HFD + Troxerutin group, and Troxerutin group. Troxerutin was treated by daily oral administration at doses of 150 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 54 publications
1
22
0
1
Order By: Relevance
“…Moreover, they were suggested to decrease the energy barrier between conformational states during protein maturation to promote proper protein folding and to bind the surface-exposed hydrophobic elements of misfolded/unfolded proteins to prevent aggregate formation and degradation in ERAD pathway [87,91,92]. Although the exact mechanism of chaperoning activity of TUDCA is still unclear, it has been shown to prevent UPR malfunction and ameliorate ER stress in various cell types [21,22,[93][94][95]. TUDCA exerts these effects partially by assisting in the transfer of mutant proteins and partially by improving protein folding capacity through the activation of ATF6 [93].…”
Section: Tudca As Chemical Chaperone In Er Stress-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they were suggested to decrease the energy barrier between conformational states during protein maturation to promote proper protein folding and to bind the surface-exposed hydrophobic elements of misfolded/unfolded proteins to prevent aggregate formation and degradation in ERAD pathway [87,91,92]. Although the exact mechanism of chaperoning activity of TUDCA is still unclear, it has been shown to prevent UPR malfunction and ameliorate ER stress in various cell types [21,22,[93][94][95]. TUDCA exerts these effects partially by assisting in the transfer of mutant proteins and partially by improving protein folding capacity through the activation of ATF6 [93].…”
Section: Tudca As Chemical Chaperone In Er Stress-related Diseasesmentioning
confidence: 99%
“…TUDCA is one such compound that is known for its chaperoning activity [12][13][14][15]. Until now, various studies have demonstrated good efficiency of TUDCA in alleviating or resolving ER stress, playing a role as a chemical chaperone; however, the exact chemical interactions involved in such activity are still debatable [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that CARD3 is a nucleotide oligomerization domain (NOD)-independent nodal point of gut inflammation (Panda and Gekara, 2018). Decreased expression of NOD1/2 and interaction between NOD1/2 and CARD3 can decrease the severity of ERS (Zhang et al, 2016). It is clear that NOD1/2 and CARD3 are important mediators of ERS-induced inflammation in mouse and human cells (Keestra-Gounder et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…IRE1 kinase control of NF-κB is positioned to propagate lipolysis, but also a plethora of immune and stress responses related to NF-κB activation. It was important to define the role of IRE1-linked ER stress in regulating NF-κB and cytokines secretion because it was reported that the bacterial cell wall muropeptide sensors NOD1 and NOD2 are mediators of ER stress-induced cytokine secretion in macrophages (20,21) and in the liver (29). It was shown that thapsgargin-induced ER stress promoted macrophage secretion of Il6, which was dependent upon IRE1, NOD1/2, and RIPK2 (20,21).…”
Section: Discussionmentioning
confidence: 99%